Peranan Mahkamah Konstitusi dalam Mewujudkan Demokrasi Substantif pada Pemilu 2024 melalui Penegakan Hukum Progresif - Sadzali, Ahmad (As-Siyasi: Journal of Constitutional Law, 2022)
The 2024 election should be a momentum towards substantive democracy. Unfortunately the decision of the Constitutional Court in 2022 regarding ministers or ministerial-level state officials not having to resign from their positions when running for president election, is considered to be a bad start to the 2024 election. This research questions how the Constitutional Court can take a role in realizing substantive democracy in Indonesia especially in the 2024 election? The method used in this study is normative legal research using a paradigmatic approach, namely progressive and historical law enforcement, namely examining previous decisions of the Constitutional Court. The results of the study conclude that the Constitutional Court should be able to take a role in realizing substantive democracy in one way through progressive law. In its history, the Constitutional Court has issued progressive decisions that support the realization of substantive democracy. Such as, for example, in the decision that eventually gave birth to a theory about general election violations, namely structured, systematic and massive (TSM) and decisions that allow the use of ID cards or passports to vote